2019
DOI: 10.1002/advs.201801237
|View full text |Cite
|
Sign up to set email alerts
|

CD146‐Targeted Multimodal Image‐Guided Photoimmunotherapy of Melanoma

Abstract: For melanoma resistant to molecularly targeted therapy and immunotherapy, new treatment strategies are urgently needed. A molecularly targeted theranostic pair may thus be of importance, where the diagnostic probe facilitates patient stratification and the therapeutic companion treats the selected cases. For this purpose, flow cytometry is used to assess the CD146 level in melanoma cells. Based on YY146, a CD146‐specific monoclonal antibody, an imaging probe 89 Zr‐Df‐YY146 is synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 50 publications
0
52
0
1
Order By: Relevance
“…The main advantage of tPDT over other adjuvant therapies is the ability to selectively apply therapy to local areas and tissues of interest, thereby minimizing side effects. When combined with NIR fluorescence or nuclear imaging, its potential for clinical use as theranostic approach is highlighted even further [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of tPDT over other adjuvant therapies is the ability to selectively apply therapy to local areas and tissues of interest, thereby minimizing side effects. When combined with NIR fluorescence or nuclear imaging, its potential for clinical use as theranostic approach is highlighted even further [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…抗体, 可以识别人类10余种肿瘤. 蔡伟波等人制备了 YY146-核素 [228,236,291,373~375] 、YY146-纳米磁颗粒-荧光 素 [376] 、荧光素-YY146-核素 [219] 以及YY146-光敏 剂 [375] , 用于肿瘤可视化成像的应用研究. 这些抗体主 要集中在肿瘤成像分级评估以及术中导航, 包括神经 胶质瘤、胃癌、肺癌、肝癌、黑色素瘤、非小细胞 肺癌.…”
Section: 抗体Yy146是蔡伟波和卞修武等人制备的单克隆unclassified
“…An example is the use of Diiodo-substituted BODIPYs as a non-porphyrin photosensitizer for PDT improved the killing efficiency of melanoma B16F10 cells (Wang W. et al, 2016). Wei et al (2019) reported a type of PIT agent, IR700-YY146, achieved high therapeutic index for melanomas of relatively smaller volumes. However, the treatment efficacy for larger tumors was not ideal due to the penetration of light through skin and tissues into the large tumor.…”
Section: Introductionmentioning
confidence: 99%
“…However, the treatment efficacy for larger tumors was not ideal due to the penetration of light through skin and tissues into the large tumor. Repeated treatment and increased the energy transfer ratio of the PIT agents may be helpful to treat large and deep tumors (Mallidi et al, 2016;Wei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%